INTEGRATING TEACHING-RESEARCH IN A CRITIC AND TRANSFORMING PRACTICE - Enedina Soares; Raimunda Magalhães da Silva; Raimundo Augusto Martins Torres (Universidade Federal do Paraná, 2000)
This study was based on a theorical perspective derived from teaching practice, in wich teaching and research are conductors and re-conductors elements of a pedagogic, transforming, critic and constructive praxis whose objective is to integrate the student's knowledge to the master and graduation courses of Nursing at the Federal University of Ceará. The study was held during the second semester of 1997 and participated 26 students regularly registered at the Reaserch Elements discipline. During the development of the didatic-pedagogic proposal one could notice that was possible to effect the integration between graduation and post-graduation in order to construct a new paradigm for the research, wich is able to change the relationships between teachers and students in producting knowledge during teaching and research activities.